Women's Empowerment Through Training in Making Melinjo Leaf Chips with Low Purine and Oil in Bulakan, Cikedung Village, Mancak District, Serang Regency - Nurtiana, Winda; Johan, Eva; Januarsi, Yeni (Yayasan Rahmat Islamiyah, 2026)
Posyandu Aster, Cikedung Village, Mancak District has potential that can be developed, namely Bulakan melinjo leaf chips (Damelkan). These chips have the weakness of being bitter due to the high purine content in melinjo leaves and the high oil content in the chips. Therefore, purine and oil reduction training was carried out using a spinner. The method used was workshops and training with the object of Aster posyandu members. The results of the training are that Aster posyandu members can apply it well and it is hoped that it can be used to produce good Damelkan chips, so that it can increase sales and the economy of Aster posyandu members. The conclusion of this activity was that Posyandu Aster was very helpful in developing the Damelkan chips produced.